In-Silico Riboswitch Based Drug Design for SARS 1 (International Journal of Scientific Research in Science and Technology, 2024)
Protein from the coronavirus causing severe acute respiratory syndrome (SARS-CoV) is responsible for binding to and identifying amino acid residues that are important for the synthesis of S1 with ACE2. It aids in the creation of antiviral inhibitors and experimental research. Anatomical models of the SARS-CoV S1 protein in fuse with human ACE2 were created in this study. One riboswitch depict for one strain of SARS Virus and five inhibitors have been classified for this riboswitch by virtual screening. These inhibitors seen to be free from the side effects of anti-viral agents.